(untitled) (Fiep Bulletin - online, 2014)
The objective of the present work is to analyze the resulted obtained in the alteration of the students’ of a gymnastics academy corporal composition submitted to the specific training "Body for Life", proposed by Phillips & D´Orso, that was adopted by this academy with the intention of marketing improvement, promising fat loss and increase of muscular mass, that is, just resulted aesthetic, however it is known that, this improvement can also introduce important changes in the quality of life, through the prevention of a series of diseases associated to the weight excess. The methodology elapses of a competitive study of statistical relevance. The sample consisted of 33 individuals, being 20 of the feminine gender and 13 of the masculine, average of age 24,79 32,78, users of the Prodígio Academia, of the area east, of the city of João Pessoa. The data were collected in the records of the physical evaluations, which were obtained weight, percentile of fat, IMC, corporal fat and thin mass. The analytic plan used the database of the statistical program SPSS, with descriptive statistics of average, standard deviation and standard error, values maximum and minimum of the evaluations in each variable, before and after the specific training, and after than was applied the test "T" of Student for matched data and the coefficient of correlation of Pearson for manipulation of variables of cut 0,007 for moderate classification with level of trust of 5%. The results revealed that there is difference between before and after in the training "Body for Life" in users of academies during the period of three months. Conclusion: the program demonstrated to be adapted in the change of the participants’ corporal composition, causing an increase of muscular mass, reduction of corporal fat and corporal mass, it is suggested the use of a diet it still specifies to maximize the results, because this procedure was optional to the participants, and few adopted it.